The ichthyofauna from the Tacuarembó Formation (Late Jurassic of Uruguay): a review and new findings - Soto, Matías (2023)
This work reviews and updates the knowledge of the fish fauna (ichthyofauna) from the Late Jurassic Tacuarembó Formation in Uruguay. Over the past decades, numerous discoveries have expanded the record of ganoid fishes, coelacanths, lungfishes, and chondrichthyans. Notable finds include the semionotiform “Walther’s fish,” new specimens of Mawsonia gigas (coelacanth), and Priohybodus arambourgi (a hybodontid shark). Lungfishes identified as Arganodus tiguidiensis dominate the dipnoan remains. These taxa represent the southernmost global occurrences of their groups and indicate a freshwater paleoenvironment. Comparisons reveal affinities with Jurassic and Cretaceous fish faunas from Brazil, North Africa, and the Arabian Peninsula, rather than with those from Tanzania or Argentina.